The Moderating Role Of Organizational Citizenship In The Relationship Between Organizational Change’s Soft Components And Operational Efficiency Promotion -Field Study On The Two Telecommunications Companies Operating In Syria, Syriatel And MTN- (Latakia University Journal - Economic and Legal Sciences Series, 2024)
In the context of this research, the impact of soft components of change management (motivation, HR policies, and innovation) on the operational efficiency of organizations is investigated using the organizational citizenship as a modifying variable in this relationship. Referring to the literature review within the scope of this research, the researchers found a positive correlation between the aforementioned organizational change management factors and the operational efficiency of operations. In order to verify this relationship, the researcher surveyed of 143 employees of organizational development departments in the Syrian private telecommunications sector during the year 2023 using a questionnaire and based on a theoretical model drawn from the RBV in organizations.As a result of the statistical analysis, the research accepted the significant impact of change management on operational efficiency through the studied independent sub-variables, and it was found that the modifying organizational citizenship variable maintains the significance of motivation only in the relationship between change management and operational efficiency. This is consistent with many previous studies that emphasized the strengthening of leadership patterns and communication with internal clients of change in organizations as a major determinant in the success of organizational change initiatives, while not neglecting the roles of HR role and innovation as essential variables in achieving the desired strategic goals of organizations.